2020
DOI: 10.1177/0001839220922133
|View full text |Cite
|
Sign up to set email alerts
|

Quo Vadis? From the Schoolyard to the Courtroom

Abstract: Existing theories exploring how companies interact with the law stop short of unveiling whether and why companies can differentially pursue, interact with, and benefit from a particular legal environment. We theorize that companies can use social structures—shared educational and professional affiliations—between lawyers and judges to strategically pursue specific legal jurisdictions, influence judges’ discretion, and ultimately reap different legal outcomes from the same legal environment. Using data on such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 111 publications
(111 reference statements)
0
9
0
Order By: Relevance
“…Corporations tend to prioritize (Cheng and Groysberg, 2018) and engage in ongoing levels of nonmarket activity to monitor the regulatory environment (Drutman, 2015). Nonmarket strategy can also be reactive: corporations often ramp up nonmarket activities when regulatory issues come to a head (Short and Toffel, 2010), or strategically arbitrage into more-favorable regulatory venues (Rao, Yue, and Ingram, 2011; Sytch and Kim, 2021). Scholars have also found that the rules governing an industry can be malleable, allowing firms to shape the meaning or interpretation of regulations in their broader legal environment (Edelman and Suchman, 1997).…”
Section: Theoretical Background: Managing Uncertainty In Nascent Indu...mentioning
confidence: 99%
“…Corporations tend to prioritize (Cheng and Groysberg, 2018) and engage in ongoing levels of nonmarket activity to monitor the regulatory environment (Drutman, 2015). Nonmarket strategy can also be reactive: corporations often ramp up nonmarket activities when regulatory issues come to a head (Short and Toffel, 2010), or strategically arbitrage into more-favorable regulatory venues (Rao, Yue, and Ingram, 2011; Sytch and Kim, 2021). Scholars have also found that the rules governing an industry can be malleable, allowing firms to shape the meaning or interpretation of regulations in their broader legal environment (Edelman and Suchman, 1997).…”
Section: Theoretical Background: Managing Uncertainty In Nascent Indu...mentioning
confidence: 99%
“…Beyond studying common ownership in the media, scholars may further probe this theory by examining the channels used by other outsiders, such as judges, politicians, activists, and securities analysts. Sytch and Kim (2021) showed that companies can strategically use shared educational and professional affiliations between lawyers and judges to influence legal outcomes, alluding to biases among judges. Although U.S. federal judges are required to recuse themselves if they have a financial stake in a litigant company, they can rule on cases related to the rivals of companies in which they invest.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to frame a thought and present it most persuasively to an audience is an important part of the ideation process (Perry-Smith and Mannucci, 2017; Falchetti, Cattani, and Ferriani, 2022). Individuals are also more susceptible to the ideas of others who share their own perspective (Kaplan, 2008) or their language style (Ireland and Pennebaker, 2010; Kovacs and Kleinbaum, 2020; Sytch and Kim, 2021). Those with high cultural embeddedness are more likely to share perspectives and language styles with many others in the organization and, therefore, to be able to frame their novel ideas most persuasively.…”
Section: Theory and Hypothesismentioning
confidence: 99%